The Effect Of Using Brainstorming Strategy In Second Students Intermediate Achievement And Decision Making Skills In Mathematics - . Rabab Abd Hussein / Shaymaa Kareem Hassoon ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The recent research aims to identify The Effect Of Using Brainstorming Strategy In Second Students Intermediate Achievement And Decision Making Skills In Mathematics. To a chive this aim, the two researchers formulated the following hypothesis: 1 – There is no statistically significant difference at (0.05) level of significance between Achievement Students of the experimental group who were taught Mathematics of using Brainstorming Strategy and level of significance Achievement Students of the control group who were taught same article by the traditional method 2 - There is no statistically significant difference at (0.05) level of significance between test decision making skills Students of the experimental group who were taught Mathematics of using brainstorming strategy and level of significance test decision making skills Students of the control group who were taught same article by the traditional method The sample of the research was limited by students second intermediate class, in on of the schools in Misan governorate, in the first semester for the academic year (2019-2018) B.A. The two researchers adopted the experimental design with the first two groups as experimental and the second control, The sample contains (60) students so the experimental group consists of (30) students and the control group also consists of (30) students, The two groups were equalized on the variables (the previous knowledge test in mathematics, age counted by month, the last achievement in mathematics). The prepared of Achievement test consisting of (40) items, the authenticity of the content has been verified, The Kiodr equation 20 was used to calculate the reliability to Achievement test, difficulty level, discrimination power and the activity of the wrong alternative of the test. The two researchers also approved a ready made test ( Hayder Saleh Mahdi AL- janaby) to measure students decision making skills Was used (t-test) to the two groups to treat the data. The results: 1 – There is a statistically significant difference at (0.05) level of significance between the mean scores of the two groups and it was in favor of the experimental group in the Achievement test. 2 - There is a statistically significant difference at (0.05) level of significance between the mean scores of the two groups and it was in favor of the experimental group in the test of decision making skills. It is the conclusions reached teaching by brainstorming Strategy shares in upgrading the students Achievement in mathematics prescribed for the second intermediate grade and increase their decision making skills The two researcher have made some suggestions and recommendation according to what have introduced.